The Relationship between Glycemic Control and Peripheral Neuropathy in Patients with Type 2 Diabetes Mellitus - Nasya Amelia Putri; Mohammad Arifin Noor; Suyanto Suyanto (International Journal Of Health Science, 2026)
People with diabetes mellitus are prone to various complications, uncontrolled blood sugar increases the risk of peripheral neuropathy. The purpose of this study is to determine the relationship between blood sugar control and peripheral neuropathy in patients with type 2 diabetes mellitus. This study employed a quantitative, non-experimental design with a correlational approach. Data were collected using monofilament examinations and a review of medical records. The study involved 104 participants recruited via purposive sampling. Subsequently, data analysis was performed using the Chi-Square test to determine statistical significance. The results of the univariate analysis mostly had characteristics of late elderly at 32,7%, housewife occcupation at 35,6%, BMI indicating overweight at 47,1%, stage 1 hypertension with systolic blood pressure at 35,6%, and stage 2 hypertension with diastholic blood pressure at 31,7%. Uncontrolled blood glucose was 73%, and peripheral neuropathy was 81%. Bivariate analysis yielded a p-value of 0.001 (p < 0.05), indicating a statistically significant relationship between blood sugar control and peripheral neuropathy in patients with Type 2 Diabetes Mellitus.